Diversidade da recuperação de informações via internet na pesquisa e ensino Internet information retrieval diversity for research and teaching p. 143-154 - Pinto, Marli Dias de Souza; Blattmann, Ursula; Kroeff, Márcia Silveira; Tristão, Ana Maria Delazari (Revista ACB, 2005)
Argumenta a diversidade de informações disponibilizadas na Internet tanto para a pesquisa como para o ensino. Apresenta estratégias ao usuário para lidar com o acervo qualitativo on-line com intuito de realizar suas atividades de busca e recuperação da informação e conseqüentemente ampliando suas competências e habilidades nesse ambiente da informação on-line. Sugere aspectos práticos no gerenciamento de documentos on-line. Recomenda aplicação de critérios de avaliação de documentos para proporcionar o acesso e evitar o excesso de informações. Descreve o uso da Internet em cursos de stricto-sensu Mestrado em Engenharia Civil, Educação Física e Administração. Abstract: Argue about the information diversity disposable in the Internet for researching and teaching. Presents strategies for the user to deal with information on-line quantity with intention to reach through activities and increase ability and competencies to recovery and access information. Give some examples about practical steps to deal with on-line document management. It recommends evaluation criteria for documents to provide access and to prevent the information overload. Describes internet use at three masters courses (stricto-sensu) Civil Engineering, Physical Education and Business Administration. Keywords: Information retrieval; Information access; Internet - Education; Internet – Research; Civil engineering; Sport Science